Physiological and biochemical characterization of the assai palm (Euterpe oleracea Mart.) during seed germination and seedling growth under aerobic and anaerobic conditions - Gonçalves, José Francisco de Carvalho; Lima, Renata Braga Souza; Fernandes, Andréia Varmes; e Borges, Eduardo Euclydes de Limae E.; Buckeridge, Marcos Silveira (Revista Árvore, 2010)
Physiological and biochemical aspects of assai palm during seed germination and early seedling growth were investigated. Seeds collected from plants growing in flooded and upland forests were used to determine the influence of normoxic (aerobic) and anoxic (anaerobic) conditions in germination and the initial and average time of development in the roots and shoots. After 75 days, seedlings germinated under normoxia were transferred to trays and submitted to flooding. Seed reserves (lipids, proteins, soluble sugars and starch) were monitored for quiescent and germinated seeds maintained under normoxic and anoxic conditions, as well as after 5, 10 and 20 days of seedling growth. Alcohol dehydrogenase (ADH) activity was quantified in roots and leaves of seedlings without or with flooding (partial and total). Seeds were not able to germinate under anoxia. Different strategies of storage mobilization of lipids, proteins, soluble sugars and starch were observed in seeds of each environment. ADH activity was induced by anoxia, with the highest level observed in the leaves. This study showed that, under normoxic conditions, the best developmental performance of assai palm seeds, from flooded or upland forest areas, during germination was associated with primary metabolites mobilization and seedling flooding tolerance with increased ADH activity. We conclude that the assai palm is well adapted to the anoxic conditions provoked by flooding.
Caracterização fisiológica e bioquímica durante a germinação de sementes e o crescimento de plântulas de açaí (euterpe oleracea mart.) sob condições aeróbica e anaeróbica
Keywords: Euterpe Edulis; Euterpe Oleracea